Lumber Disc Herniation in Adult and Low Back Pain: Prospective Study in Bangladesh - Uddin Ahmad, Jamal; Huq Siddiqui, Erfanul; Rahman, Md. Moshiur; Alinoor, Md.; Mia, Md. Ibrahim (Journal of Neonatal Surgery, 2025)
Background: Low back pain (LBP) is a prevalent health issue globally, often attributed to lumbar disc herniation (LDH), which can severely affect individuals' quality of life and productivity. In Bangladesh, the increasing incidence of LBP due to LDH poses significant health and socioeconomic challenges, yet limited research exists on the factors influencing this condition within the local population. Objective: This prospective study aims to investigate the prevalence, clinical characteristics, and outcomes of LDH among adults experiencing LBP in Bangladesh, focusing on demographics, occupational backgrounds, lifestyle factors, and the effectiveness of treatment modalities. Method: Conducted over a specified period, this study enrolled 100 adults aged 30 years and above presenting with LBP symptoms confirmed by MRI. A structured questionnaire collected demographic data, pain characteristics, and occupational histories. Standardized pain scales quantified symptom severity, and statistical analysis, including odds ratios (OR), assessed the relationship between demographic factors and LDH prevalence. Results: Among the participants, 60.5% reported continuous pain, primarily exacerbated by activities such as walking (65.2%) and bending (74.3%). The cohort exhibited a male predominance (58%) and the highest LDH prevalence in the 50-59 age group (OR 2.1, p = 0.04). MRI findings confirmed that the L4/L5 disc level had the highest incidence of herniation types, with protrusions being the most common. Conclusion: This study underscores the critical association between age and the development of LDH, particularly in middle-aged adults. The results indicate a need for targeted pain management strategies and further exploration of demographic influences on LDH among Bangladeshi patients. Understanding these factors can enhance clinical practices and inform future research on LBP and LDH management.